The Role of Bacterial and Fungal Microbiomes in Enhancing Plant Tolerance to Environmental Stresses - Younis, Abdul-Rahman Jarjees (American Journal of Biology and Natural Sciences, 2026)
In this study, a completely randomized design (CRD) in four treatments was applied: non-inoculated (control), PGPR-inoculated, fungal-inoculated and PGPR-fungal co-inoculated. The study showed a substantial increase in growth attributes of inoculated plants over the control. Plant height increased from 10.5 ± 0.6 cm to 20.3 ± 1.0 cm, root length from 8.2 ± 0.5 cm to 17.8 ± 0.9 cm, fresh weight from 2.0 ± 0.2 g to 5.4 ± 0.5 g, and dry weight from 0.40 ± 0.05 g to 1.20 ± 0.08 g. Inoculation with B. licheniformis also lowered the levels of oxidative stress markers, with MDA content dropping from 6.9 ± 0.3 to 2.5 ± 0.1 nmol/g FW and H₂O₂ content from 5.8 ± 0.2 to 2.3 ± 0.1 μmol/g FW. Antioxidant enzyme activities were markedly enhanced, with SOD increasing from 24.5 ± 1.2 to 60.5 ± 2.0 U/mg protein, CAT from 18.0 ± 1.0 to 55.2 ± 1.8 U/mg protein, and POD from 19.5 ± 1.1 to 58.0 ± 1.7 U/mg protein. Physiological characteristics were also significantly enhanced, with proline content increasing from 2.0 ± 0.1 to 6.0 ± 0.3 μmol/g FW and chlorophyll content from 1.3 ± 0.1 to 3.1 ± 0.2 mg/g FW. Root colonization studies validated the establishment of the inoculants, with CFU increasing from undetectable levels in the control to 5.6 ± 0.3 × 10⁶ g⁻¹ soil in the co-inoculated plants. These results indicate that combined PGPR and beneficial fungi inoculation is a feasible and sustainable approach to improve plant tolerance to stress under challenging environmental conditions.